2016
DOI: 10.1016/j.amjsurg.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Thinking like an expert: surgical decision making as a cyclical process of being aware

Abstract: BACKGROUND-Education researchers are studying the practices of high-stake professionals as they learn how to better train for flexibility under uncertainty. This study explores the "Reconciliation Cycle" as the core element of an intraoperative decision-making model of how experienced surgeons assess and respond to challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
(43 reference statements)
0
29
0
Order By: Relevance
“…6 Sayra et al proposed the concept of reconcilation cycle, which constituted the iterative process of gaining and transforming information. 7 They observed that the cyclical nature of a surgeon's decision making implied that a higher degree of awareness was needed for transforming information. The factors governing these decisions, although interesting, is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…6 Sayra et al proposed the concept of reconcilation cycle, which constituted the iterative process of gaining and transforming information. 7 They observed that the cyclical nature of a surgeon's decision making implied that a higher degree of awareness was needed for transforming information. The factors governing these decisions, although interesting, is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these questions always seem to be calibrated at the task level, the most elementary component of a surgical procedure. A task consists of three stages that must be performed by the surgical trainee: the motor action that transforms the patient's anatomy; an evaluation of its effect, and the selection of the next motor action . Collections of such tasks define a particular part or step in the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A task consists of three stages that must be performed by the surgical trainee: the motor action that transforms the patient's anatomy; an evaluation of its effect, and the selection of the next motor action. [34][35][36] Collections of such tasks define a particular part or step in the surgical procedure. In total hip replacement surgery, the procedure of choice in this study, surgical trainees carry out 44 different steps between the incision of the skin and the final suture, each varying in complexity.…”
Section: And Nowmentioning
confidence: 99%
“…Additional research from Cristancho et al (22), on how expert cognition develops found that those clinicians with less experience focused on information at a physiological or pathophysiological level, in contrast to experts who subconsciously focused on "the bigger picture," more readily putting new data into the clinical context. Our study did not demonstrate a significant evolution of analytical-tointuitive processes with increasing experience; however, this may be due to a lack of awareness amongst the respondents on the subtleties of their decision-making processes (23).…”
Section: Intuitive and Analytical Decision-making Is Positively Assocmentioning
confidence: 99%